Cholix protein domain I functions as a carrier element for efficient apical to basal epithelial transcytosis. Issue 1 (2nd January 2020) - Taverner, Alistair; MacKay, Julia; Laurent, Floriane; Hunter, Tom; Liu, Keyi; Mangat, Khushdeep; Song, Lisa; Seto, Elbert; Postlethwaite, Sally; Alam, Aatif; Chandalia, Apurva; Seung, Minji; et al.
ABSTRACT: Cholix (Chx) is expressed by the intestinal pathogen Vibrio cholerae as a single chain of 634 amino acids ( 70.7 kDa protein) that folds into three distinct domains, with elements of the second and third domains being involved in accessing the cytoplasm of nonpolarized cells and inciting cell death via ADP-ribosylation of elongation factor 2, respectively. In order to reach nonpolarized cells within the intestinal lamina propria, however, Chx must cross the polarized epithelial barrier in an intact form. Here, we provide in vitro and in vivo demonstrations that a nontoxic Chx transports across intestinal epithelium via a vesicular trafficking pathway that rapidly achieves vesicular apical to basal (A→B) transcytosis and avoids routing to lysosomes. Specifically, Chx traffics in apical endocytic Rab7 + vesicles and in basal exocytic Rab11 + vesicles with a transition between these domains occurring in the ER-Golgi intermediate compartment (ERGIC) through interactions with the lectin mannose-binding protein 1 (LMAN1) protein that undergoes an intracellular re-distribution that coincides with the re-organization of COPI + and COPII + vesicular structures. Truncation studies demonstrated that domain I of Chx alone was sufficient to efficiently complete A→B transcytosis and capable of ferrying genetically conjoined human growth hormone (hGH). These studies provide evidence for a pathophysiological strategy where native Chx exotoxin secreted in the intestinal lumen by nonpandemic V. cholerae can reach nonpolarized cells within the lamina propria in an intact form by using a nondestructive pathway to cross in the intestinal epithelial that appears useful for oral delivery of biopharmaceuticals. One-Sentence Summary : Elements within the first domain of the Cholix exotoxin protein are essential and sufficient for the apical to basal transcytosis of this Vibrio cholerae -derived virulence factor across polarized intestinal epithelial cells.